Influência de modificações superficiais na resistência à corrosão e na bioatividade da liga beta ti-40nb para aplicações biomédicas - Ricci, Virgilio Pereira (2021)
β-titanium (Ti) alloys have great applicability in the biomedical area due to properties such as low density, high corrosion resistance, low elasticity modulus (E), and biocompatibility. However, these alloys are not bioactive. It is necessary to make surface modifications producing bioactive surfaces and with better electrochemical properties. For these reasons, this work evaluated the bioactivity performance and corrosion resistance of the Ti-40Nb alloy modified superficially by anodization, producing the amorphous nanostructures of nanotubes (NTs-AM) and nanopores (NPs-AM). Initially, the annealing was carried out on anodized samples with amorphous nanostructure to reduce the alloy’s E and crystallize the amorphous nanostructures in a mixture of anatase and rutile, obtaining these characteristics with annealing at 550 °C, namely NTs-HT and NPs-HT. The precalcification (PC) process was performed to increase the bioactive behavior of NTs-HT and NPs-HT, that is, NTs-PC and NPs-PC. The electrochemical behavior was studied by open circuit potential (OCP), potentiodynamic polarization, and electrochemical impedance spectroscopy (EIS). Samples with NTs-HT and NPs- HT showed the highest corrosion potential (Ecorr) and lower passivation current density (ipass), with the lowest ipass of ~0,3 μA/cm² being observed in NPs-HT. The EIS simulation by equivalent electrical circuits (EEC), the NPs-HT showed greater resistance and thickness of the barrier layer. After 14 days of soaking in SBF, it was not observed HAp formation in the unmodified substrate, NTs/NPs- HT conditions exhibited moderate apaite formation. In contrast, NTs/NPs-PC samples showed high apatite formation, with apatite mass gain ~3.5x higher than anodized and annealed samples.